PELATIHAN PERANCANGAN DESAIN PACKAGING SISWA SMKN 1 DENTE TELADAS - Rohiman Rohiman; Desiana Muryasari; Rika Febri Sasmita; Rahmattulloh Ramadhoni (LPPM Universitas Bina Bangsa, 2023)
Packaging design is a form of visual communication that uses images to convey information or messages as effectively as possible. The provision of graphic design training to students at SMK Negeri 1 Dente Teladas aims to provide students with graphic design knowledge and skills so that students can use these skills in designing posters and brochures. This service is carried out in 2 stages, the first stage is identification and data collection and in stage 2 the evaluation the output achieved in this activity is the product packaging design produced by students. The analysis of the work produced received the response from the service partners, which was very useful and able to increase students' knowledge of SMKN 1 Dente Teladas about the importance of packaging for marketing a product and learn the importance of the creative process in a design process. Students should continue to learn on an ongoing basis to understand the technicalities in designing visual communication design products which will be very useful for them when they enter the industrial world